Effect of pH on the formation of disinfection byproducts in swimming pool water - is less thm better? - Willach, Sarah; Hansen, Kamilla M S; Mosbæk, Hans; Albrechtsen, Hans-Jørgen; Andersen, Henrik Rasmus; Antoniou, Maria G. (My University, 2012)
This study investigated the formation and predicted toxicity of different groups of disinfection byproducts (DBPs) from human exudates in relation to chlorination of pool water at different pH values. Specifically, the formation of the DBP groups trihalomethanes (THMs), haloacetic acids (HAAs), haloacetonitriles (HANs) and trichloramine (NCl 3), resulting from the chlorination of body fluid analog, were investigated at 6.0 ≤ pH ≤ 8.0. Either the initial concentration of active chorine or free chlorine was kept constant in the tested pH range. THM formation was reduced by decreasing pH but HAN, and NCl 3 formation increased at decreasing pH whereas the formation of HAAs remained constant. Under our experimental conditions, the formation of NCl 3 (suspected asthma inducing compound) at pH = 6.0 was an order of magnitude higher than at pH = 7.5. Furthermore, the effect of the presence of bromide on DBP formation was investigated and found to follow the same pH dependency as without bromide present, with the overall DBP formation increasing, except for HAAs. Estimation of genotoxicity and cytotoxicity of the chlorinated human exudates showed that among the quantified DBP groups, HAN formation were responsible for the majority of the toxicity from the measured DBPs in both absence and presence of bromide.
Keywords: Hydrogen-ion concentration; Swimming pools; Trihalomethanes; Chlorine; Water--Analysis; Trihalomethanes